Interrupting Short-Circuit Direct Current Using an AC Circuit Breaker in Series with a Reactor. (1st October 2012) - Kulkarni, Saurabh; Santoso, Surya
Abstract : This paper describes and demonstrates the principle and efficacy of a novel direct current fault interruption scheme using a reactor in series with a controlled rectifier and a conventional AC circuit breaker. The presence of the series reactor limits the capacitive discharge current from the DC filter capacitor at the output terminals of the phase-controlled rectifier. In addition, the series reactor along with the filter capacitor forms an underdamped series RLC circuit which forces the fault current to oscillate about zero. This synthetic alternating current can then be interrupted using a conventional AC circuit breaker. The selection criteria for the series reactor and overcurrent protection are presented as well. Using the proposed scheme for an example case, a DC fault current magnitude is reduced from 56 kA to 14 kA, while the interruption time is reduced from 44 ms to 25 ms.